Oroxin B Attenuates Ovariectomy-Induced Bone Loss by Suppressing Osteoclast Formation and Activity - Huang JM; Wang CZ; Lu SY; Wang Z; Yan ZQ (Dove Medical Press, 2021)
Jun-ming Huang, Chen-zhong Wang, Shun-yi Lu, Zhe Wang, Zuo-qin Yan Department of Orthopaedics, Zhongshan Hospital, Fudan University, Shanghai, 200032, People's Republic of ChinaCorrespondence: Zuo-qin Yan 180 Feng Lin Road, Xuhui District, Shanghai, 200032, People's Republic of ChinaEmail yan.zuoqin@zs-hospital.sh.cnBackground: Osteoclasts are the major players in bone resorption and have always been studied in the prevention and treatment of osteoporosis. Previous studies have confirmed that a variety of flavonoids inhibit osteoporosis and improve bone health mainly through inhibiting osteoclastogenesis. Oroxin B (OB) is a flavonoid compound extracted from traditional Chinese herbal medicine Oroxylum indicum (L.) Vent, exerts potent antitumor and anti-inflammation effect, but its effect on osteoclastogensis remains unknown.Methods: We comprehensively evaluated the effect of OB on the formation and function of osteoclasts and the underling mechanism by bone marrow-derived macrophage in vitro. In vivo, we used mice ovariectomized model to verify the protective effect of OB.Results: OB was found to inhibit osteoclast formation and bone resorption function in vitro, in a dose-dependent manner and the increased osteoclastic-related genes induced by RANKL (NFATc1, c-fos, cathepsin K, RANK, MMP9 and TRAP) were also attenuated following OB treatment. Mechanistical investigation showed OB abrogated the increased phosphorylation level of MAPK and NF-κB pathway, and diminished the expression of the vital transcription factors for osteoclastogenesis. OB also prevented ovariectomy (OVX)-induced bone loss by inhibiting osteoclast formation and activity in mice.Conclusion: Our study demonstrated that OB may act as an anti-osteoporosis agent by inhibiting osteoclast maturation and attenuating bone resorption.Keywords: osteoclast, Oroxin B, MAPK, NF-κB, RANKL, osteoporosis